Prioritising and ranking critical factors for sustainable cloud ERP adoption in SMEs. (2015) - Bharathi, S. Vijayakumar; Mandal, Tanuja
The cloud ERP enables the SMEs to join the race of the largest competitive organisations to achieve and sustain competitive growth. There are several factors which play an important role in the decision making of the SMEs, whether to go for ERP as a service or not. This study brings out the ranking and prioritising of critical factors which will help the ERP service providers to better understand the expectations of the SME clients. This exploratory research was conducted on a selected set of consultants, implementing partners and SMEs of ERP. Analytic hierarchy process (AHP) was used to prioritise and rank the critical factors to be considered for adopting cloud ERP. A set of 17 critical factors was initially categorised on the basis of cost, security, organisational factors, performance and functionality of ERP. The study found that amongst others, cost related factors like subscription fees, maintenance cost and implementation cost featured in the top five ranking critical factors. Other significant factors included SLA conditions, BCP and DR, IT resources cost, data confidentiality. The outcome of this research provides an authentic reference to the stakeholders while planning and executing sustainable information system adoption like cloud ERP.